CERITA ARJUNA TAPA SEBAGAI MEDIA PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI UNTUK PENGUATAN KARAKTER DISIPLIN SISWA KELAS X DI SMK N 3 SUKAWATI KABUPATEN GIANYAR - I Gusti Putu Ngurah Angga Divayana; Gusti Nyoman Mastini; Ni Made Suyeni (PT. Hasba Edukasi Mandiri, 2026)
Hindu teachings are derived from the Vedas, which are challenging for students to understand, believe in, and practice. Therefore, relevant methods are needed to enable students to grasp them, such as storytelling. One traditional story for building student character is the story of Arjuna Tapa, which depicts Arjuna's spiritual journey to achieve holiness and a deeper understanding of himself, the world, and his relationship with God. The purpose of this research is to determine the structure, function, and meaning of the Arjuna Tapa story as a medium for Hindu religious education and character education to strengthen the disciplined character of class X students at SMK N 3 Sukawati. The results of this study are: 1) The structure of the Arjuna Tapa story consists of an introduction (premise and purpose of asceticism), the process of asceticism and sacrifice, the granting of gifts and forms of teaching, and the application of teachings in everyday life. 2) The function of the Arjuna Tapa story includes learning about challenges and sacrifices in the asceticism process, perseverance in facing tests, consistency in carrying out tasks, achievement through discipline and sacrifice, and being an example for others. 3) The meaning of the Arjuna Tapa story includes perseverance in achieving goals, self-control and resisting temptation, sacrifice as part of discipline, consistency in effort, responsibility towards oneself, strength in simplicity and sincerity, and achievement through disciplined effort.